Belarusian scientific texts on journalism in 2010–2020: topics and terminology - Fedotova, Natallia A. (Journal of the Belarusian State University. Journalism, 2022)
The article is devoted to the analysis of the priority directions of the Belarusian journalistic science, the characteristics of national specifics in research on journalism and media. The result of the study of Belarusian scientific texts in 2010–2020 allows to identify thematic gaps, as well as to identify the similarities and differences between the Belarusian and Russian scientific research in the field of journalism.